2017
DOI: 10.1371/journal.pone.0188190
|View full text |Cite
|
Sign up to set email alerts
|

Active immunization in patients transplanted for hepatitis B virus related liver diseases: A prospective study

Abstract: IntroductionProphylactic administration of hepatitis B immunoglobulin (HBIG) and nucleos(t)ide analogues (NAs) is the standard treatment for controlling hepatitis B virus (HBV) recurrence after liver transplantation (LT). Since lifelong use of HBIG is expensive and inconvenient and the antibodies level in anti-hepatitis B surface (HBs) is not sustainable and stable, an alternative strategy is to produce anti-HBs antibodies by active immunization. Our present study aimed to prospectively investigate the efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
(30 reference statements)
0
7
0
1
Order By: Relevance
“…As the biggest immune organ, the liver plays an important role in immune responses. 18 C-reactive protein (CRP) is an acute phase reactant protein considered as a diagnostic indicator of early inflammation, which is synthesized by the liver. 19 Furthermore, the liver is engaged in inflammation, and elevated inflammation will cause liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…As the biggest immune organ, the liver plays an important role in immune responses. 18 C-reactive protein (CRP) is an acute phase reactant protein considered as a diagnostic indicator of early inflammation, which is synthesized by the liver. 19 Furthermore, the liver is engaged in inflammation, and elevated inflammation will cause liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…A single-center prospective study to investigate the efficacy and safety of active vaccination in patients was conducted, in which each patient was given double doses of the intramuscular vaccine at 0, 1, 2, 6 and 12 months of enrollment, with a follow up period of 6 months after completion of the vaccine protocol. 59 Out of 27 men included in this study, 9 were responders (33.3%). All the patients in this study were at least 1-year post-LT and were HBsAg-and HBV DNA-negative, with normal liver functions.…”
Section: Role Of Active Vaccinationmentioning
confidence: 94%
“…Patients’ response to HBV vaccination is influenced by their immune status. In their prospective study, Yang et al suggested baseline lymphocyte‐to‐eosinophil (LY/EO) ratio as a potential biomarker in identifying best candidates among HBV transplant recipients for HBV vaccination, as it was negatively correlated with patients’ immune system status 82 . Of 27 patients transplanted for HBV‐related liver disease, low (<15) LY/EO ratio was observed in the majority of nine responders to HBV vaccination (8/9, 89%), whereas the majority of non‐responders (11/18, 63.64%) had high LY/EO ratio 82 .…”
Section: Prevention Of Post‐lt Hbv Recurrencementioning
confidence: 99%
“…In their prospective study, Yang et al suggested baseline lymphocyte‐to‐eosinophil (LY/EO) ratio as a potential biomarker in identifying best candidates among HBV transplant recipients for HBV vaccination, as it was negatively correlated with patients’ immune system status 82 . Of 27 patients transplanted for HBV‐related liver disease, low (<15) LY/EO ratio was observed in the majority of nine responders to HBV vaccination (8/9, 89%), whereas the majority of non‐responders (11/18, 63.64%) had high LY/EO ratio 82 . Owing to immunosuppression, LT recipients have different levels of innate or acquired tolerance to HBsAg, therefore, long‐term and repetitive antigenic stimulation is often required, in order to develop adequate immune response, which can be reinforced with booster vaccination if necessary 83 …”
Section: Prevention Of Post‐lt Hbv Recurrencementioning
confidence: 99%